Preparation and Characterization of Nano Crystalline Cellulose from Bamboo Fibers by Controlled Cellulase Hydrolysis (Journal of Fiber Bioengineering and Informatics, 2012)
The extracellular cellulase enzyme produced by Trichoderma reesei was used to prepare NanocrystallineCellulose (NCC) by controlled hydrolysis of bamboo fibers. The morphology of the prepared bamboocellulose nanocrystals was characterized by field emission scanning electron microscopy and thecrystallinity was measured by X-ray diffraction. The degree of polymerization was tested by automaticviscosimeter. The surface charge in suspension was estimated by Zeta-potential. The results showedthat all NCC from bamboo fibers presented a rod-like shape, an average diameter of 24.7 nm and lengthof 286 nm, with an aspect ratio of around 12. The zeta potential of cellulase hydrolyzed NCC was 4times lower than that of NCC prepared by acid hydrolysis process.
Keywords: Nanocrystalline Cellulose; Bamboo Fibers; Trichoderma Reesei; Cellulase; Characterization